Hypernatremia in Newborns: A Practical Approach to Management - Dr. Naveed Ur Rehman Durrani (18262147) (2022)
Hypernatremia is a potentially serious condition in both term and preterm babies, which can lead to severe and permanent neurological damage. There are many physiological changes in sodium homeostasis that occur soon after birth. Understanding this physiological process, early anticipation of hypernatremia and familiarization with the neonatal management of hypernatremia can prevent mortality and long-term morbidity associated with this condition. This review aims to provide a practical and understandable approach to the diagnosis and management of hypernatremia in neonates. Other Information Published in: Biomedicine Hub License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1159/000524637